Can different small-sided game formats impact physiological, physical, technical, and tactical demands in basketball players? A systematic review with meta-analysis - Li, Tingyu; Wang, Shuang; Martinho, Diogo; Silva, Rui Miguel; Gouveia, Élvio; Clemente, Filipe (Biology of Sport, 2025)
This systematic review with meta-analysis aimed to compare the effects of different game formats (1v1, 2v2, 3v3, 4v4, 4v3, 3v3+1, and 5v5) on basketball players’ physiological, physical, technical, and tactical responses during SSGs. The data sources utilized were PubMed, Scopus, SPORTDiscus, and Web of Science. Eligibility included basketball players of any age or sex, competing in tier 2 or higher, exposed to at least two different formats. Studies had to report on physiological responses, physical demands, technical performance, and tactical behaviors. Methodological quality was assessed using the MINORS scale. The search identified 4,967 titles, with 16 articles eligible for the review and meta-analysis. Results indicated that extreme SSGs (e.g., 1v1, 2 v2) elicited significantly higher cardiovascular demands, as reflected by greater mean and peak heart rates, compared to larger SSGs (e.g., 3v3, 4v4), with a moderate effect size favoring extreme formats (Hedge’s g = -0.47, p = 0.02). In terms of perceived exertion (RPE), no significant differences were found between extreme and larger SSGs, suggesting similar subjective effort across formats. For technical performance, extreme SSGs (e.g., 1v1, 2v2) exhibited a higher frequency of actions, such as passes and shots, compared to larger formats, with a moderate effect size favoring smaller formats (Hedge’s g = -0.78, p < 0.01). No significant publication bias was found, though high heterogeneity was noted in RPE comparisons. This meta-analysis showed that extreme SSG formats elicit higher cardiovascular demands and more frequent technical actions than larger formats, highlighting their potential for targeting specific physical and technical demands in basketball training.